"The Low Principles of Jurisprudence": Legal Indeterminacy in Edmund Burke's Impeachment of Warren Hastings. Issue 3 (2020) - Goodman, Rob
Abstract: Edmund Burke's impeachment of Warren Hastings for his conduct as governor-general in India represented the era's most serious internal challenge to British imperialism. But the impeachment's legal and institutional implications have been neglected. The central points of contention were the nature of impeachment in Britain and the nature of law in India. Burke insisted that impeachment must override the "low" and "mean" standards of the common law, yet he celebrated India for its dense judicial institutions. Hastings took the opposite position, demanding that the impeachment adhere strictly to the common law, yet defending his conduct in India by appeal to its political expediency, rather than its lawfulness. Each found himself in a "rhetorical contradiction, " alternately arguing in praise of, and in critique of, legal reasoning and procedures. While Hastings attempted to surmount the contradiction through the discourse of realism, Burke turned to the discourse of natural law—a language of lawfulness without legalism.